Aromatherapy in anxiety, depression, and insomnia: A bibliometric study and visualization analysis - Xia Cao; Jiansong Zhou; Jiali Liu; Hui Chen; Wei Zheng (Heliyon, 2023)
Aromatherapy is a natural treatment method that uses essential oils (EOs) extracted from aromatic plants; EOs and their components exhibit a wide range of pharmacological activities, with a special focus on their implementation toward mental disorders, such as anxiety and depression. This study aimed to identify the scientific output and activity related to aromatherapy in anxiety, depression, and insomnia through bibliometric approaches. In this bibliometric study, we utilized CiteSpace and VOSviewer to evaluate the Web of Science Core Collection publications and to build visualizing maps to analyze the research progress on this topic between 2001 and 2021. A total of 1159 original and review articles in English, published in 578 different peer-reviewed journals by 260 authors, were identified. In the recent two decades, there was a steady increase in the number of published articles, especially in the following five years. All publications were distributed among 88 countries/regions. The United States had the most publications, with 188 (16.22%) articles, followed by China [131 (11.30%)], Brazil [110 (9.49%)], and Japan [85 (7.33%)]. Most studies were published in the Journal of Ethnopharmacology, and Physiology & Behavior was the most cited journal. Hritcu L was the top published scientist and Gupta SC was the most frequently co-cited. The knowledge base of this field research mainly included the related efficacy of aromatherapy/EOs, application status, and biochemical mechanism. And the keyword co-occurrence analysis revealed that the topics “oxidative stress,” “chemical composition,” “systematic review,” and “sleep quality” were research frontiers. In conclusion, this comprehensive bibliometric study provides an updated perspective on research hotspots of aromatherapy in anxiety or depression and developmental tendencies of natural remedies for mental health. In addition, this study could also provide valuable information for research teams, practitioners, and decision-makers when designing and implementing natural treatment methods for mental health-promoting interventions for individuals with mood disorders.